African & American : West Africans in Post-Civil Rights America - Halter, Marilyn; Johnson, Violet Showers (Book collections on Project MUSE., 2014)
"African & American tells the story of the much overlooked experience of first and second generation West African immigrants and refugees in the United States during the last forty years. Interrogating the complex role of post-colonialism in the recent history of black America, Marilyn Halter and Violet Showers Johnson highlight the intricate patterns of emigrant work and family adaptation, the evolving global ties with Africa and Europe, and the translocal connections among the West African enclaves in the United States. Drawing on a rich variety of sources, including original interviews, personal narratives, cultural and historical analysis, and documentary and demographic evidence, African & American explores issues of cultural identity formation and socioeconomic incorporation among this new West African diaspora. Bringing the experiences of those of recent African ancestry from the periphery to the center of current debates in the fields of immigration, ethnic, and African American studies, Halter and Johnson examine the impact this community has had on the changing meaning of 'African Americanness' and address the provocative question of whether West African immigrants are, indeed, becoming the newest African Americans"--Provided by publisher.